Methodologies for improving technology decision making for sustainable socio-economic development - Ferreira, F. A. F.; Ferreira, J. J. M. (Technology in Society, 2023)
The importance of technology and knowledge management in societal development has long been recognized. However, decision problems in the current context have been complicated by an ever-greater degree of complexity, forcing decision makers to seek out new approaches and methodologies that facilitate the processes that support decision making [1]. Although epistemological differences exist between the different branches of operational research/management science (OR/MS), all of them share a focus on decision aid. These decision-making methods constitute valuable tools for structuring and evaluating complex decision situations, and can allow for more informed, potentially better decisions.